Distribution of benthic macroinvertebrates across a reed stand in a brackish Baltic lagoon - Krzysztof Pawlikowski; Ryszard Kornijów (Oceanologia, 2022)
The role of reeds in the functioning of ecosystems and their significance for zoobenthos in the coastal lagoons is poorly understood. We hypothesise that next to the spatial zonal differentiation of abiotic factors in the apparently homogeneous habitat of reeds, benthic macroinvertebrate fauna is also unevenly distributed, and differs in taxonomic and functional diversity, as well as density and biomass across the reed stand. The research was carried out in the Vistula Lagoon (southern Baltic) along three designated sectors arranged parallel to the shoreline and differing in distance from the shore and depth. Mean density of reed stems in the analysed stand was within the range of values reported from different American and European wetlands. Regardless of the location within the reeds and the season, the fauna was dominated by detritivorous Tubificinae and larvae of Chironomidae. The highest diversity, density, and biomass of fauna were found in the middle littoral zone, and the lowest in the outer zone adjacent to the open water. The presented data support our hypothesis predicting the existence of a spatial variation pattern in the composition and distribution of macroinvertebrates in response to the changing zonal habitat conditions within the reed stand.